Practical considerations for the use of mTOR inhibitors. Issue 1 (December 2015) - Diekmann, Fritz; Campistol, Josep
Abstract Immunosuppressive therapy after kidney transplantation is based on calcineurin inhibitors (CNI). In most cases CNI therapy is combined with mycophenolate and steroids. In spite of good short-term results this therapy is associated with long-term toxicities, graft loss and patient death. Therefore, alternative immunosuppressive strategies are needed that combine excellent efficacy with low incidences of long-term adverse outcomes. This review focuses on the strategies based on mTOR- inhibitors in combination with minimized exposure to CNI.